Serotonin modulates the voltage dependence of delayed rectifier and Shaker potassium channels in Drosophila photoreceptors. - Hevers, W.; Hardie, R.C. (Neuron, 1995)
We describe the in situ modulation of potassium channels in a semi-intact preparation of the Drosophila retina. In whole-cell recordings of photoreceptors, rapidly inactivating Shaker channels are characterized by a conspicuously negative voltage operating range; together with a delayed rectifier, these channels are specifically modulated by the putative efferent neurotransmitter serotonin. Contrary to most potassium channel modulations, serotonin induced a reversible positive shift in the voltage operating range, of +30 mV for the Shaker channels and +10-14 mV for the delayed rectifier. The maximal current amplitudes were unaffected. Modulation was not affected by the subunit-specific Shaker mutations ShE62 and T(1;Y)W32 or a null mutation of the putative modulatory subunit eag. The modulation of both channels was mimicked by intracellularly applied GTP gamma S.